An approach to improve the efficiency of cooling enhancement of a thermoelectric refrigerator through the use of phase‐change materials - Xin Chen; Ruo‐ji Zhang (Energy Science & Engineering, 2024)
Abstract In this study, a technique is suggested to enhance the temperature difference for cooling and energy efficiency of thermoelectric cooler (TEC) used in cooled detectors when subjected to high current conditions. Embedding a structure for storing heat during phase change is the basis of this method at the heat sink. A simulation model was created for a common two‐stage series TEC with an asymmetrical design, which is coupled with a structure for storing heat through phase change. The research examined how phase transition heat storage impacts the coefficient of performance (COP) and refrigeration temperature difference across various phase‐change substances, heat transfer coefficients at the hot end, currents, and the height of the phase‐change material (PCM). The findings suggest that the suggested approach of combining PCM with TEC can efficiently lower the cold end temperature of TEC by a maximum of 20 K, enhance the temperature gap by a maximum of 16 K, and preserve the consistency of the optimized quantity across various hot end heat transfer coefficients. During the phase‐change process of PCMs, the COP of TECs integrated with PCM is found to increase by an average of 2%–3% compared to TECs without PCM integration. Under the maximum current operating condition, the cryogenic temperature can be optimized to a minimum of 238 K. In summary, the proposed method of integrating phase‐change heat storage with TECs provides a promising solution for improving their cooling performance and energy efficiency in cooled detectors under high current conditions. Additional investigation can be conducted to explore the practical application of this approach and enhance the design parameters for various uses.